Exploring the Relationship Between Growth Hormone Secretagogue Receptor (GHSR) Gene and Body Proportions in Bangkok Chickens: Insights from DNA Sequencing and Hin6I Enzyme-Restricted PCR-RFLP Analysis - Syaikhullah, Gayuh; Hertamawati, Rosa Tri; Adhyatma, Muhammad (Universitas Airlangga, 2024)
The purpose of this study was to determine the diversity of the growth hormone secretagogue receptor (GHSR) gene and also to analyze the association of the GHSR gene with the body proportions of Bangkok chickens. A total of 125 Bangkok chickens were reared, and blood samples were taken. Bangkok chickens were kept in colony cages with ad libitum feeding and drinking. The GHSR gene polymorphism was determined using the PCR-RFLP method. The restriction enzyme used in this study was Hin6I. The data analyzed were indicators of body proportions, which included data on body weight, carcass weight, and commercial cut weight. Single nucleotide polymorphism (SNP) identification using the Molecular Evolutionary Genetics Analysis 7 program with reference number AB095994.1. Allele frequency values, genotype frequencies, and Hardy-Weinberg balance values were also analyzed. The association between the GHSR gene and the traits observed in Bangkok chickens was analyzed using the T-test. The results of the study showed that the GHSR gene in Bangkok chickens had two genotypes, namely TT and CT. The values for Ho and He were 0.224 and 0.198, respectively. The genotype frequencies of TT and CT were 0.776 and 0.224, respectively. The two genotypes were associated with body weight, carcass weight, and commercial weight (p < 0.05). For all measured criteria, the TT genotype showed a higher weight value than the CT genotype. The GHSR gene has the potential to be used as a genetic marker for the selection process on body weight, carcass weight, and commercial weight traits.